Conservation of 87Sr/86Sr During Wine-Making of White Wines: A Geochemical Fingerprint of Geographical Provenance and Quality Production - Tescione, Ines; Casalini, Martina; Marchionni, Sara; Braschi, Eleonora; Mattei, Massimo; Conticelli, Sandro (Frontiers in Environmental Science, 2020)
The measuring of 87Sr/86Sr in wine, grape and bioavailable soil fraction samples with the same uncertainty of geological materials allows to fully compare the whole wine-production chain with the peculiar geochemical isotope signature of any geographic area. Indeed, this signature is the same that the final product inherited by the soil bioavailable fraction and, in turn, by the geological substratum of the vineyard. On the other hand, the few data available in literature referred to white wines cast doubts for the use of this geographic tracer due to the common use of geological-derived additives, such as bentonite, in the white wine-making procedure, which may overprint the original geochemical signature of the vineyard substratum. To tackle this issue, we analysed the Sr-isotope compositions of four white wines produced over a period of almost 10 years in a high-quality organic farm, located on the volcanic units of the Vulsini Volcanic District (southern Tuscany, Italy). The 87Sr/86Sr values of rock, soil, grape, grape juice, must, and wine were compared among them and furtherly weight against the isotope fingerprint of the bentonite and yeast employed during the wine-making process. The 87Sr/86Sr values from the entire white-wine production chain reveal that no variations are observed from the signature imprinted by the original geological substratum (rocks and soils), suggesting that no further contribution is given by the addition of bentonite and yeast to the white wine Sr-isotope values. On the other hand, intermediate 87Sr/86Sr compositions are found when grapes from different vineyards are used for making multi-cultivar wine blends. Indeed, the experimental data clearly show that the Sr isotope composition is maintained through the wine-making process for white as well as for red wines. Both grape and final wine preserved the isotope signature inherited from the labile fraction of the soil where the vines are farmed. Our data thus confirm, also for white wines, the robustness of Sr-isotope tool in studies where it is important to define terroirs and geographic provenance.